Human pluripotent stem cells on artificial microenvironments: a high content perspective - Viswanathan, Priyalakshmi; Gaskell, Terri; Moens, Nathalie; Culley, Oliver J.; Hansen, Darrick; Gervasio, Mia K. R.; Yeap, Yee J.; Danovi, Davide (Frontiers in Pharmacology, 2014)
Self-renewing stem cell populations are increasingly considered as resources for cell therapy and tools for drug discovery. Human pluripotent stem (hPS) cells in particular offer a virtually unlimited reservoir of homogeneous cells and can be differentiated towards diverse lineages. Many diseases show impairment in self-renewal or differentiation, abnormal lineage choice or other aberrant cell behavior in response to chemical or physical cues. To investigate these responses, there is a growing interest in the development of specific assays using hPS cells artificial microenvironments and high content analysis. Several hurdles need to be overcome that can be grouped in: (i) availability of robust, homogeneous and consistent cell populations as a starting point; (ii) appropriate understanding and use of chemical and physical microenvironments; (iii) development of assays that dissect the complexity of cell populations in tissues while mirroring specific aspects of their behavior. Here we review recent progress in the culture of hPS cells and we detail the importance of the environment surrounding the cells with a focus on synthetic material and suitable high content analysis approaches. The technologies described if properly combined have the potential to create a paradigm shift in the way diseases are modelled and drug discovery is performed.